1996
DOI: 10.1111/j.1399-302x.1996.tb00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of host responses on the pathogenicity of strains of Porphyromonas gingivalis

Abstract: Porphyromonas gingivalis is implicated in the etiology of periodontitis. Strains of P. gingivalis have been classified as invasive or noninvasive based on their ability to form abscesses in a mouse model. The purpose of this study was to investigate the ability of P. gingivalis strains to cause abscesses and periodontal bone loss in an experimental rat model and the effect of serum and salivary responses on the pathogenicity of these strains. Subcutaneous injection of animals with P. gingivalis 33277, A7A1-28,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 40 publications
4
55
0
1
Order By: Relevance
“…Like that in many encapsulated pathogenic bacteria, capsule expression in P. gingivalis is linked to pathogenicity. Interestingly, strains that produce a capsule have been shown to cause a spreading type of infection in mice, with recovery of the organism from blood, spleen, and kidneys (16,52), while infections with strains that do not synthesize capsule (strains 381 and 33277) typically attach and result in localized abscesses (43,52), suggesting that encapsulation is linked to dissemination and not attachment. Our results show that capsule expression in P. gingivalis blocks biofilm formation and hence could enhance dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Like that in many encapsulated pathogenic bacteria, capsule expression in P. gingivalis is linked to pathogenicity. Interestingly, strains that produce a capsule have been shown to cause a spreading type of infection in mice, with recovery of the organism from blood, spleen, and kidneys (16,52), while infections with strains that do not synthesize capsule (strains 381 and 33277) typically attach and result in localized abscesses (43,52), suggesting that encapsulation is linked to dissemination and not attachment. Our results show that capsule expression in P. gingivalis blocks biofilm formation and hence could enhance dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…The form and partitioning of Kgp between the cell and the extracellular milieu have been reported to show variations (28) that correlate with distinct changes in the functional properties of P. gingivalis strains (12,22). Differences have also been observed in the pathogenic potential of laboratory strains, depending on the animal model (4,13) or the in vitro assay employed (10,11). The latter differences in virulence may be a function of the heterogeneity within virulence genes such as kgp.…”
mentioning
confidence: 90%
“…While animal studies have demonstrated the pathogenicity of mono-infections of periodontopathogens such as P. gingivalis [13][14][15][16][17], in recent years, reports have been published on the effects of mixed microbial infections including P. gingivalis and A. actinomycetemcomitans [18], P. gingivalis and F. nucleatum [19] and P. gingivalis and B. forsythus [20] which resulted generally in increased levels of pathogenicity with a synergistic effect observed in the humoral and cellular host responses. In the human, F. nucleatum colonizes the plaque prior to P. gingivalis and high levels of F. nucleatum have been demonstrated in association with P. gingivalis as well as other bacteria associated with periodontal disease, such as B. forsythus, Prevotella intermedia and Eikenella corrodens [21].…”
Section: Introductionmentioning
confidence: 99%